D’un océan à l’autre: spatialité de la parole et lisibilité des lieux chez Jacques Poulin - Bruera, Franca; Marino, Valeria (Ponti/Ponts, 2021)
In Jacques Poulin’s Volkswagen Blues maps are not only a fundamental part of a physical, imaginary and identity space, but also the pivotal structure of a complex narrative space. This paper will focus on how Saint-Laurent and other rivers find a place in this widest cartographic imagination, considered as the symbolic and ordering principle of the novel. Christian Jacob’s thoughts and reflections on the history of cartography will serve as the basis of our novel’s analysis, which aspires to create a dialogue between literature and cartography.